Les révoltes au pays de la révolution - Kamel Chachoua (Revue des Mondes Musulmans et de la Méditerranée)
Much of the Algerian intelligentsia in general and social scientists in particular were critical or, at the very least skeptical about the “Arab revolts” as spring 2011. How can we explain such a reaction from a generation of intellectuals, scholars, academically and politically trained and socialized in the first decade of independent Algeria, then considered as the “Mecca of revolutionaries”, “um al-thawarat “ or the “Lighthouse of the Third World “ ? This study will attempt to show how this posture is the dual expression of virulent nationalism filled with Marxist ideology of the 1960-70s on the one hand, and a positivist, scientistic unconscious inherited from the philosophical tradition of Ecole Normale and Paris. This dual source may explain the character both “revolutionary” and “conservative” of this pioneering elite of independent Algeria.Algeria, Sociology, Algerian intelligentsia, Nationalism, Social movements, Algerian exception, Arab revolts